Features interference EMG leg extensor muscles of skilled players in the context of the special exercises - Sirenko, P.A.; Korolinska, S.V.; Sirenko, Y.P. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The article considers the problems of improvement of physical training of skilled players. The main instrumental method of the research is electromyography. The aim of the research is determination of the optimal angle of the provisions of legs on her hips for the appearance of a maximum of bioelectric activity of the muscles of the front panel hips in exercise unbending legs sitting on the mechanical simulator. In the course of research we have worked for electromyography 10 players of FC Metalist at the age of 19 – 30 years during the five-second of the submaximum contraction of these muscles as: musculus rectus femoris, musculus vastus medialis, musculus vastus lateralis. The results of the analysis of segments of electromyography allowed to make a conclusion, that we investigated the provisions of the angle of 140 degrees has the lowest preconditions for the appearance of muscle strength. We have obtained data testify to the fact that the angle of 90 degrees is the position of the greatest preconditions for the appearance of muscle strength.